An Effective Industrial Practicum Training Program for Operations Management Students in Malaysia - Mohd Shariff, Sariwati (2007)
The objective of industrial training is to provide students an exposure to the real working world. It has been generally assumed that students in industrial training will learn something in the organization; the roles and responsibilities in providing the practicum training are left solely to the industry; trainees are not demonstrating the intended skills; training evaluation lacks assessment on the trainees’ learning outcomes and the practicum guidelines are inadequate. It is now a concern for the institution of higher education to know whether the industrial training program is effective for the students. Henceforth, the purpose of the study was to investigate on the factors of an effective industrial training program from the trainees’ perspectives, and the learning processes in an effective training. This study adopted the constructivist approach, focusing on the trainees’ perspectives where they described in their own words, expressions and reflections on the practicum experiences based on realities at work. A qualitative methodology was used to seek in depth understanding on the trainees’ experiences, and the researcher was the instrument in data collection. This study adopted in depth interview technique with Operations Management students from Faculty of Business Management of a local public university as participants for this study. Twelve participants were purposively selected by the Head of program and practicum advisors. Interviews were taped recorded and transcribed with accuracy. The validity and rigor of data analysis were assured through triangulation, members check and peers review, and researcher’s bias and assumptions were declared in the study. The study found that there were five factors contributed to effective practicum training: host organization, roles of facilitator, learning curriculum, roles of trainee and learning. The study showed that trainees’ motivation, readiness to learn, self directedness and their roles contributed towards effective practicum. Ten learning processes were identified: observation, doing, solving, social interaction, work situations, self learning, experience, reflections, feedback and evaluation. The trainees’ practicum training was effective based on three learning outcomes: cognitive development in acquiring work knowledge, behavioral development in possessing job skills and work experience, and personal development in attaining attitudinal values and self actualization. This study concluded with: both host organization and trainee must be selective for practicum attachment; trainee’s characteristics influenced their roles in practicum; practicum training served as informal learning for students and that transfer of learning occurred at the work place; and a comprehensive practicum evaluation to measure the effectiveness of practicum. This study provided implications to the body of knowledge whereby five factors for effective practicum training program were: host organization, facilitator, trainee, institution and learning curriculum. As for implication to practice, industrial training guidelines and comprehensive practicum evaluation system needed to be established as a standard for an effective practicum. Recommendations were put forth to improve the industrial training program: to strengthen the practicum curricula structure and to establish training guidelines; to prepare the mindsets of the trainees before practicum attachment; to improve the training evaluation system; and trainees’ welfare and compliances to the related legislations at work place.